A Critical Analysis of Healthcare Accessibility and Equity in Multidisciplinary Settings - Alzamanan, Abdullah Saleh; Alsaab, Mansour Abdullah; Al Saab, Mohammed Ali Mohammed; Alzubaidi, Nawaf Saleh Hussain; Al Grad, Mana Mohammad H; AlQirad, Hamad Mohammed Hamad; Al Samah, Hamad Mubarak Hussain; AL Salah, Moamad Jaber Morshed; Al Khuraim, Wabran Ali Salem; Al Khuraim, Saleh Ali Salem; Assiri, Jameela Eissa; Al Duways, Adel Saleh Hadi (Journal of Ecohumanism, 2024)
Universal healthcare and healthcare disparity remain major hurdles to effective health delivery systems worldwide, including major health sectors designed to offer complex, interprofessional care. In this paper, barriers, including socioeconomic differences, organizational or systemic prejudice, and resource distribution within the healthcare system, are the focus of the discussion. Through a review of the literature and quantitative data analysis, we identify areas of inaccessibility and provide recommendations for improving equality in a large interprofessional healthcare team. These insights confirm that coordinated, integrated care increases a patient's health benefits but that much of the gap remains unconsidered by standard and integrated care models.